Effect of Ternary Eutectic Salt on the Calcium Sulfate Oxygen Carrier for Chemical Looping Combustion of Coal Char. Issue 3 (26th September 2016) - Zhang, Pengfei; Ding, Ning; Li, Huijun; Lv, Mingming; Guan, Ning; Liu, Zhigang
Abstract: The effect of a ternary eutectic salt (43.5 % Li2 CO3 –31.5 % Na2 CO3 –25 % K2 CO3 ) on the CaSO4 oxygen carrier for chemical looping combustion (CLC) of coal char is experimentally investigated in a bench‐scale fluidized‐bed reactor with steam as the gasification agent at atmospheric pressure and 925 °C. The ternary eutectic catalyst is added to the CaSO4 oxygen carrier by physical mixing and impregnation, respectively. The enhanced carbon conversion and shortened reaction time in the fluidized bed reactor, coupled with the high weight loss rate of CaSO4 reduction with CO in the thermogravimetric analyzer (TGA), suggest that the reactions of coal char gasification and CaSO4 reduction are synergistically catalyzed in the presence of the ternary eutectic salt. The modified oxygen carriers prepared by physical mixing and impregnation show no significant difference in carbon conversion and gasification rates according to the experimental results. The sample with catalyst impregnated into the mixture of anhydrite and coal char gives higher activity compared to the samples with catalyst impregnated into the coal char or anhydrite solely, due to the more uniform distribution of the catalyst. Abstract : Catalysis worth its salt : Experiments on iG‐CLC of coal char using a CaSO4 oxygen carrier modified by the ternary eutectic salt (43.5 % Li2 CO3 –31.5 % Na2 CO3 –25 % K2 CO3 ) are conducted in a bench scale fluidized‐bed reactor. The addition of the ternary eutectic salt synergistically facilitates the gasification process and CaSO4 reduction reaction. The alkali carbonate compounds (LiKCO3 and LiNaCO3 ) in the ternary eutectic salt show better catalytic activity than a separate salt mixture of the same composition.